Photon-counting detector CT: a disrupting innovation in medical imaging - Akos Varga-Szemes; Tilman Emrich (European Radiology Experimental)
Abstract Over the past decades, computed tomography (CT) imaging has profited from various technical innovations. Besides improvements such as higher temporal and spatial resolutions, lower radiation dose, and the introduction of dual- and multi-energy imaging, the development and recent clinical introduction of photon-counting detector CT (PCD-CT) represents a milestone with the potential to substantially change clinical CT imaging and expand its indications. This thematic series of European Radiology Experimental comprises a collection of original research papers and review articles demonstrating the benefits and challenges of this cutting-edge technology. The thematic series includes a wide range of relevant topics spanning from initial clinical experiences using PCD-CT to original research papers covering potential applications in various body regions.